Pathophysiology of NAFLD and NASH in Experimental Models: The Role of Food Intake Regulating Peptides - Kořínková, L. (Front Endocrinol (Lausanne), 2020)
Obesity, diabetes, insulin resistance, sedentary lifestyle, and Western diet are the key factors underlying non-alcoholic fatty liver disease (NAFLD), one of the most common liver diseases in developed countries. In many cases, NAFLD further progresses to non-alcoholic steatohepatitis (NASH), fibrosis, cirrhosis, and to hepatocellular carcinoma. The hepatic lipotoxicity and non-liver factors, such as adipose tissue inflammation and gastrointestinal imbalances were linked to evolution of NAFLD. Nowadays, the degree of adipose tissue inflammation was shown to directly correlate with the severity of NAFLD. Consumption of higher caloric intake is increasingly emerging as a fuel of metabolic inflammation not only in obesity-related disorders but also NAFLD. However, multiple causes of NAFLD are the reason why the mechanisms of NAFLD progression to NASH are still not well understood. In this review, we explore the role of food intake regulating peptides in NAFLD and NASH mouse models. Leptin, an anorexigenic peptide, is involved in hepatic metabolism, and has an effect on NAFLD experimental models. Glucagon-like peptide-1 (GLP-1), another anorexigenic peptide, and GLP-1 receptor agonists (GLP-1R), represent potential therapeutic agents to prevent NAFLD progression to NASH. On the other hand, the deletion of ghrelin, an orexigenic peptide, prevents age-associated hepatic steatosis in mice. Because of the increasing incidence of NAFLD and NASH worldwide, the selection of appropriate animal models is important to clarify aspects of pathogenesis and progression in this field.